A chromosomal radiosensitivity study of a population of radiation workers using the micronucleus assay. (1st January 2003) - Thierens, H.; Aousalah, B.; Vral, A.; Ridder, L. De; Barbe, M.
The micronucleus (MN) assay already applied to the biomonitoring of radiation workers is a relatively easy and fast technique allowing assessment of the individual chromosomal radiosensitivity status of radiation workers on a large scale. A pilot study was set up to evaluate the chromosomal radiosensitivity in a group of 99 male radiation workers from the nuclear power plant Doel in Belgium. Heparinized blood samples of the workers were divided into three parts: one served for the assessment of a possible effect of occupational exposure on the number of micronuclei, the two others served for the assessment of individual chromosomal radiosensitivity by the increase of the number of micronuclei after 1 and 2 Gy in vitro γ-irradiation. For each worker, date of birth, smoking habit and previous medical exposures were registered. Furthermore the external radiation burden accumulated over the last 10 years was calculated from the personnel dosimetry records. Concerning the MN frequency as a biomarker for effect, the present study confirms the strong increase of MN frequency with age and the tendency of an increase with an accumulated radiation burden, observed in previous studies. Using the MN frequency after in vitro irradiation as a biomarker for chromosomal radiosensitivity, the data of the present study do not support a lowered radiosensitivity in radiation workers due to the adaptive response mechanism induced by occupational exposure. As the overall in vitro radiation induced MN frequency distributions can be represented by a normal distribution without a high frequency tail, none of the workers can be considered as exceptionally by radiosensitive with the test. Further validation of the MN assay as a radiosensitivity assay for a population of workers is necessary.